Efecto antialimentario del extracto vegetal de Enterolobium cyclocarpum (Jacq) Griseb sobre la termita de madera seca Incisitermes marginipennis (LATREILLE) (ISOPTERA:KALOTERMITIDAE) - Urrutia Hernández, Sara Eliet (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The antimicrobial effect of aqueous extract of heartwood Enterolobium cyclocarpum (Jacq) Griseb on bacteria of clinical interest was determined, the bacteria used in the study are causing nosocomial infections. The results show that seven of the thirteen bacteria used showed a bacteriostatic effect in the presence of aqueous extract. In vitro and in situ were performed using the intestinal content of dry wood termite Incisitermes marginipennis (Latreille) on which the toxic effect of aqueous extract of the heartwood of E. cyclocarpum was determined. The termite gut contents was grown on Mueller Hinton Agar plates, Sabouraud Agar and Blood Agar Base in anaerobic and aerobic conditions in all bacterial growth media was obtained. Were obtained eight first intestinal bacterial isolates termite marginipennis I. dry wood. Five of the bacterial isolates exhibit a bacteriostatic effect in the presence of the aqueous extract, two of which have a bactericidal effect with the aqueous extract and three have a bacteriostatic effect with the ethanol extract. In determining the toxic effect in situ dry wood termite, tests gavage and termite gut contents was observed in a first test microscopically immersion objective and classified and accounted forms found were performed.

Se determinó el efecto antimicrobiano del extracto acuoso de duramen Enterolobium cyclocarpum (Jacq) Griseb sobre bacterias de interés clínico, las bacterias utilizadas en el estudio son causantes de infecciones intrahospitalarias. Los resultados obtenidos muestran que siete de las trece bacterias utilizadas presentaron un efecto bacterióstatico en presencia del extracto acuoso. Se realizaron ensayos in vitro e in situ utilizando el contenido intestinal de la termita de madera seca Incisitermes marginipennis (Latreille) sobre los cuales se determinó el efecto tóxico del extracto acuoso del duramen de E. cyclocarpum. El contenido intestinal de la termita fue cultivado en placas de Agar Mueller Hinton, Agar Sabouraud y Agar Base Sangre, en condiciones de anaerobiosis y aerobiosis, en todos los medios se obtuvo crecimiento bacteriano. Se obtuvieron por primera vez ocho aislados bacterianos intestinales de la termita de madera seca I. marginipennis. Cinco de los aislados bacterianos presentan un efecto bacterióstatico en presencia del extracto acuoso, dos de ellos presentan un efecto bactericida con el extracto acuoso y tres presentan un efecto bacterióstatico con el extracto etanólico.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias en Farmacología Básica
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2007-0016; Extracto; Enterolobium cyclocarpum; Termita; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2889